Genome-Wide Analysis Reveals Changes in Polled Yak Long Non-coding RNAs in Skeletal Muscle Development - Ma, Xiaoming; Fu, Donghai; Chu, Min; Ding, Xuezhi; Wu, Xiaoyun; Guo, Xian; Kalwar, Qudratullah; Pei, Jie; Bao, Pengjia; Liang, Chunnian; Yan, Ping (Frontiers in Genetics, 2020)
Long non-coding RNAs (lncRNAs) have been extensively studied in recent years. Numerous lncRNAs have been identified in mice, rats and humans, some of which play important roles in muscle formation and development. However, little is known about lncRNA regulators that affect muscle development in yak (Bos grunniens). LncRNA expression during skeletal muscle development in yak was analyzed by RNA sequencing at three development stages: three years (group A), six months (group M) and 90-day-old fetuses (group E). A total of 1,180 lncRNAs were identified in the three development stages. Compared with group E, 154 were upregulated and 130 were downregulated in group A. Compared with group A, 31 were upregulated and 29 were downregulated in group M. Compared with group E, 147 were upregulated and 149 were downregulated in group M (padj < 0.001, |log2FC|>1.2). In addition, functional annotation analysis based on gene ontology (GO) and the Kyoto protocol encyclopedia of genes and genomes (KEGG) database showed that differentially expressed lncRNAs were cis-trans target genes. The results showed that differentially expressed lncRNAs were mainly involved in PI3K-Akt signaling pathway, focal adhesion, MAPK signaling pathway, apoptosis and p53 signaling pathway. Furthermore, RTL1, IGF2, MEF2C, Pax7 and other well-known muscle development regulators were included in a co-expression network of differentially expressed target genes and lncRNAs. These data will help to further clarify the function of lncRNAs in the different stages of skeletal muscle developmental in yak.